Üniversite Öğrencilerinin Özgecilik ve Otantiklik Seviyeleri Arasındaki İlişkinin İncelenmesi - (:unkn) unknown (My University, 2016)
Bu makale, üniversite öğrencilerinin özgecilik ve otantiklik seviyelerinin ince- lenmesi amacıyla ilişkisel tarama yöntemiyle dizayn edilmiştir. Çalışmada, Marmara Üniversitesi Atatürk Eğitim Fakültesi'nde öğrenim görmekte olan 314 öğrenciye Kişisel Bilgi Formu, Özgecilik Ölçeği ve Otantiklik Ölçeği uygulanmış; yapılan ayıklama işle- minin ardından bunların 291'i analize tabi tutulmuştur. Verilerin analizinde, değişkenler arasındaki ilişkiyi belirlemek için Pearson korelasyon analizi ve grupların aritmetik or- talamaları arasındaki farklılıkları belirlemek için bağımsız gruplar t testi kullanılmıştır. Sonuç olarak, üniversite öğrencilerinin özgecilik ile otantiklik seviyeleri arasında an- lamlı bir ilişkiye rastlanmamıştır.

Altruism, which means helping others voluntarily, has been the main subject of many researches for 30 years. The concept of altruism was first described as 'the tendency and desire to live for others' by the French sociologist and philosopher Auguste Comte in the nineteenth century (Karadağ andMutafçılar, 2009). In the dictionary of psychological terms, Erkuş (1994) describes the altruism as benefit-making behavior on a voluntary basis and without waiting for a reward. In another definition, altruism is defined as a motivational state in which the ultimate goal is to increase the welfare of someone else (Batson and Shaw, 1991). In general, the key point in these definitions is that the person in altruist behavior is motivated to help without any reward expectation (Blagg, 2011). Authenticity that is described as behaving in a way compatible with individual's own values, preferences, and needs or true self has also taken place among the major concepts discussed in recent years. Wood, Linley, Maltby, Baliousis, and Joseph (2008) examine the concept of authenticity in a three-dimensional structure. According to this, the authenticity consisting of self-alienation, authentic life and acceptance of external influences is expressed as a structure in which the true self of the person is not obstructed (Goldman and Kernis, 2002). When the concepts of altruism and authenticity are examined together, lots of questions will come into view. How authentic is a person who acts for the good of others and devotes himself to the authority of others?Do being authentic and behaving altruistically constitute an obstacle, or do they have a positive relationship with each other? These mentioned questions concerning the relationship between the two concepts -altruism and authenticity- constitute the main problem of this research and in the study, the relationship between the altruism and authenticity levels of the university students is investigated. Aim of the Study Although being unique and taking care of others' needs instinctively look contradictory, the question marks diminish when these two variables are thought to be the characteristics of self-realized individuals.At this point, when the characteristics of the self-realized individual defined by Maslow are considered, it is seen that the characteristics of the self-realized individual coincide with the characteristics of both the altruist and the authentic individuals. For this reason, this study is carried out in order to investigate whether there is a relationship between the levels of altruism and authenticity of university students. Methodology This study was designed by a relational research method to investigate the levels of altruism and authenticity of university students.Relational research model is a pattern which aims to determine the interchange between two or more variables and the degree of this change(Karasar, 2000). Population and Sampling The data of the study were colected from 314 students studying at Marmara University Atatürk Faculty of Education and 291 of the data were subjected to the analysis after the extraction process.221 participants of the total are female while 70 are male. Data Collection Instruments The data used in the study was collected through Personal Information Form, Altruism Scale and Authenticity Scale. Altruism Scale In order to determine altruistic behaviors of the university students, Altruism Scale developed by Ümmet, Ekşi andOtrar (2013) was used. The scale consists of 38 items and each item was presented on 5-point Likert(1= strongly disagree to 5= strongly agree). The scale has7 sub-dimensions: Participating in Volunteer Activities (7 items), Financial Aid (6 items), Aid Under Traumatic Situations (6 items), Aid to Elderly People or Patients (4 items), Aid Based on Physical Strength (5 items), Aid in the Educational Process (5 items), Aid Based on Intimate Feeling (5 items). Authenticity Scale Authenticity was measured by using Authenticity Scale developed byWood, Linley, Maltby, Baliousis and Joseph (2008). Turkish adaptation of this scale has been done by İlhan and Özdemir (2012). The scale consists of 12 items and each item was presented on a 7-point Likert (1= does not describe me at all to 7= describes me very well) scale. The scale has three sub-dimensions: accepting external living (four items), self-alienating (four items), and authentic living (four items). Data Analysis In the analysis of the data, independent groups t-test was used to determine the differences between the means of the groups and Pearson's correlation analysis to determine the relationship between the variables. The data were analyzed by using SPSS 15.0. Findings According to the information obtained from the research, as a result of the Pearson Correlation Coefficient analysis conducted to determine whether there was a meaningful relationship between altruism and authenticity, the relationship between altruism and authenticity was not found to be significant. According to the results of the research, the scores of authenticity do not show a significant difference according to the variable of participation in the civil society organization while the scores of altruism vary. According to this result, it was found that students who participated in the civil society organization had higher scores from altruism scale.Another finding shows that both the altruism and authenticity differ according to the gender variable and the difference is in favor of the girl students. Discussion Depending on the results of our study, it's seen that there is no relationship between authenticity and altruism levels of university students. This result is inconsistent with the literature supporting the hypothesis that there is a relationship between authenticity and altruism. However, it seems that studies investigating the relationship between altruism and authenticity are not enough to make a certain conclusion. For this reason, it is possible to say thatthis study might have an important contribution for future studiesin terms of presenting a different perspective on altruism and authenticity while giving a result that is incompatible with the literature. However, there may be the missing points of this research because it is only applied to university students and limited sampling. For this reason, it is thought that studying this subject again in future and reaching larger and more diversified sampleswould be useful in order to get certain results in this subject.
Investigating Relationship Between Altruism and Authenticity Level of University Students
Keywords: Eğitim, Eğitim Araştırmaları